New products management - Crawford, Merle; Benedetto, Anthony Di (New York, 2008)
The new edition provides the reader with the management approach through a marketing perspective. Comprehensive coverage of new product development process and practice prepares the reader to manage the people and processes from a marketing perspective. The authors aim to make the textbook increasingly relevant to its users as this revision is considered to be a new product
Keywords: New Products- Mangement